2004
DOI: 10.1063/1.1807014
|View full text |Cite
|
Sign up to set email alerts
|

Spin injection from Fe3Si into GaAs

Abstract: We demonstrate room-temperature spin injection from the epitaxially grown ferromagnetic metal Fe3Si into the semiconductor GaAs. The injection efficiency is comparable to values previously obtained for the Fe∕GaAs and MnAs∕GaAs hybrid systems using the emission of similar (In,Ga)As∕GaAs light-emitting diodes for the detection of spin polarization. The temperature dependence of the detected polarization is explained by taking into account spin relaxation inside the semiconductor device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(53 citation statements)
references
References 17 publications
2
51
0
Order By: Relevance
“…In order to combine this new field of electronics with the established semiconductor technologies, spin injection from the ferromagnet into a semiconductor is essential and has already been extensively investigated [1][2][3] . The Fe 3 Si compound on GaAs has turned out to be a promising candidate of ferromagnet/semiconductor systems with its spin injection efficiency of above 2% at a temperature of 150 K and 1% at room temperature 4 . Fe 3 Si is a quasi-Heusler compound that crystallizes in the D0 3 symmetry in the chemically ordered phase with a lattice constant a =5.65Å.…”
Section: Introductionmentioning
confidence: 99%
“…In order to combine this new field of electronics with the established semiconductor technologies, spin injection from the ferromagnet into a semiconductor is essential and has already been extensively investigated [1][2][3] . The Fe 3 Si compound on GaAs has turned out to be a promising candidate of ferromagnet/semiconductor systems with its spin injection efficiency of above 2% at a temperature of 150 K and 1% at room temperature 4 . Fe 3 Si is a quasi-Heusler compound that crystallizes in the D0 3 symmetry in the chemically ordered phase with a lattice constant a =5.65Å.…”
Section: Introductionmentioning
confidence: 99%
“…These alloys have reduced magnetic anisotropy and increased resistivity when compared to pure Fe, making them interesting materials for technical applications. [1][2][3][4] In particular, special attention has been attributed to the binary Heusler alloy Fe 0.75 Si 0.25 due to its half-metallic ferromagnetic features and high Curie temperature. The magnetization relaxation of Fe 0.75 Si 0.25 /MgO(001) thin films has been studied recently.…”
mentioning
confidence: 99%
“…Th erefore, the introduction of a spin-selective barrier contact could be a very eff ective method for achieving high effi ciency of spin injection. [21]) as spin injection sources is a promising means of enhancing the effi ciency of spin injection [33,[58][59][60][61][62]. Kawaharazuka et al [33] reported on spin injection from the Heusler alloy Fe 3 Si into an InGaAs/GaAs QW structure, which achieved a circular polarization of 3% at 25 K. Dong et al [58] used a Heusler alloy Co 2 MnGe as a spin source to inject spin-polarized electrons into an Al 0.1 Ga 0.9 As/GaAs QW, aff ording an estimated spin polarization of 27% at 2 K. Damsgaard et al [62] reported a spin polarization of 6.4% at 5 K for a Co 2 MnGa spin aligner.…”
Section: Obstacles To Electrical Spin Injectionmentioning
confidence: 99%
“…[21]) as spin injection sources is a promising means of enhancing the effi ciency of spin injection [33,[58][59][60][61][62]. Kawaharazuka et al [33] reported on spin injection from the Heusler alloy Fe 3 Si into an InGaAs/GaAs QW structure, which achieved a circular polarization of 3% at 25 K. Dong et al [58] used a Heusler alloy Co 2 MnGe as a spin source to inject spin-polarized electrons into an Al 0.1 Ga 0.9 As/GaAs QW, aff ording an estimated spin polarization of 27% at 2 K. Damsgaard et al [62] reported a spin polarization of 6.4% at 5 K for a Co 2 MnGa spin aligner. Despite the prediction of larger spin polarization, to date the highest spin polarization reported remains relatively low, attributed variously to the properties of the interface, such as inhomogeneities, defects, strain and reduced symmetries, and the eff ect of fi nite temperature on the electronic, magnonic and phononic states at the interface [68][69][70].…”
Section: Obstacles To Electrical Spin Injectionmentioning
confidence: 99%
See 1 more Smart Citation